ELT-MOS White Paper: Science Overview and Requirements - Evans, C; Puech, M; Barbuy, B; Bastian, N; Bonifacio, P; Caffau, E; Cuby, J; Dalton, G; Davies, B; Dunlop, J; Flores, H; Hammer, F; et al. (2013)
The workhorse instruments of the 8-10m class observatories have become their multi-object spectrographs (MOS), providing comprehensive follow-up to both ground-based and space-borne imaging. With the advent of deeper imaging surveys from, e.g., the HST and VISTA, there are a plethora of spectroscopic targets which are already beyond the sensitivity limits of current facilities. This wealth of targets will grow even more rapidly in the coming years, e.g., after the completion of ALMA, the launch of the JWST and Euclid, and the advent of the LSST. Thus, one of the key requirements underlying plans for the next generation of ground-based telescopes, the Extremely Large Telescopes (ELTs), is for even greater sensitivity for optical and infrared spectroscopy. Here we revisit the scientific motivation for a MOS capability on the European ELT, combining updated elements of science cases advanced from the Phase A instrument studies with new science cases which draw on the latest results and discoveries. These science cases address key questions related to galaxy evolution over cosmic time, from studies of resolved stellar populations in nearby galaxies out to observations of the most distant galaxies, and are used to identify the top-level requirements on an 'E-ELT/MOS'. We argue that several of the most compelling ELT science cases demand MOS observations, in highly competitive areas of modern astronomy. Recent technical studies have demonstrated that important issues related to e.g. sky subtraction and multi-object AO can be solved, making fast- track development of a MOS instrument feasible. To ensure that ESO retains world leadership in exploring the most distant objects in the Universe, galaxy evolution and stellar populations, we are convinced that a MOS should have high priority in the instrumentation plan for the E-ELT.